TANTANGAN DAN PELUANG PEMBELAJARAN MAHARAH ISTIMA’ DI ERA DIGITAL: STUDI KASUS DI PRODI PBA UIN RADEN INTAN LAMPUNG: Penelitian Kualitatif Deskriptif dengan Desain studi kasus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study originates from the growing integration of digital technology in Arabic language instruction, particularly in the teaching of listening skills, which serve as a fundamental component of language acquisition. The conditions observed in the Arabic Language Education Program at UIN Raden Intan Lampung indicate that digital media such as audio recordings, YouTube, Google Drive, and recording applications have supported instructional activities, although several challenges remain evident. The purpose of this research is to identify the primary obstacles in teaching maharah istima’ in the digital era, to describe the opportunities emerging from technological utilization, and to formulate strategies for optimizing learning. This study employs a descriptive qualitative approach using a case study design. Data were collected through observations, interviews with lecturers and students, and analysis of instructional documents such as lesson plans and teaching materials. The findings reveal that the challenges include technical issues such as inadequate audio quality, non-soundproof classrooms, and unstable internet connectivity. Linguistic barriers, including limited vocabulary mastery and difficulty following native speakers’ pronunciation, also pose significant obstacles. On the other hand, digital media provide substantial opportunities to offer authentic audio exposure, enhance learning motivation, and facilitate students’ autonomous access to materials. The study concludes that the integration of digital technology has the potential to improve the effectiveness of maharah istima’ instruction, provided that it is supported by improved facilities, strengthened linguistic foundations, and adequate guidance from instructors.